1996
DOI: 10.1002/clc.4960190708
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous amiodarone is safe and seems to be effective in termination of paroxysmal supraventricular tachyarrhythmias

Abstract: Background: Paroxysmal atrial fibrillation (PAF) and paroxysmal supraventricular tachycardia (PSVT) leading to hemodynamic compromise are among the most common reasons for admission to the coronary care unit (CCU) and need prompt and efficient therapy. Direct current cardioversion is the therapy of choice, but if found contraindicated or unavailable some antiarrhythmie agents are usually given to restore sinus rhythm. Many of these drugs have obvious limitations, especially in patients with acute myocardial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 15 publications
2
26
2
Order By: Relevance
“…Although 2 randomized clinical trials 383,386 documented a similar PSVT conversion rate between adenosine and calcium channel blockers, adenosine was more rapid and had fewer severe side effects than verapamil. Amiodarone as well as other antiarrhythmic agents can be useful in the termination of PSVT, but the onset of action of amiodarone is slower than that of adenosine, 399 and the potential proarrhythmic risks of these agents favor the use of safer treatment alternatives.…”
Section: Therapymentioning
confidence: 99%
“…Although 2 randomized clinical trials 383,386 documented a similar PSVT conversion rate between adenosine and calcium channel blockers, adenosine was more rapid and had fewer severe side effects than verapamil. Amiodarone as well as other antiarrhythmic agents can be useful in the termination of PSVT, but the onset of action of amiodarone is slower than that of adenosine, 399 and the potential proarrhythmic risks of these agents favor the use of safer treatment alternatives.…”
Section: Therapymentioning
confidence: 99%
“…[272][273][274][275]277,278 The effectiveness of diltiazem in conversion to sinus rhythm is supported by 4 trials (LOE 1). 273,277,279,280 The evidence to support the use of other drugs for conversion to sinus rhythm is limited to a few trials for each drug, including sotalol (LOE 1), 281 amiodarone (LOE 4), 282 propafenone (LOE 1), 283 ) and nadolol (LOE 1). 284 The study on nadolol suggested treatment effect on rate as well.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Amiodarone can achieve nearly 100% efficacy in the inhibition of induced sustained reentrant SVT (LOE 6). 22 Adenosine is safe and effective in pregnancy. 23 Adenosine, however, does have several important drug interactions.…”
Section: Iv-71mentioning
confidence: 99%